Relational Aggression Victimization and Depression: Testing Self-Compassion and Self-Criticism as Moderator and Mediator - Nariswari, Anindya Ayu; Muttaqin, Darmawan (Bina Nusantara University, 2023)
The research examined the role of self-compassion and self-criticism as moderators and mediators in the relationship between relational aggression victimization and depression. Victimization of relational aggression had various negative consequences, one of which could be depression. However, few previous studies had examined moderator and mediator variables in the relationship between victimized relational aggression and depression. On the other hand, self-compassion and self-criticism could potentially be moderators and mediators between negative experiences and depression. The research used a cross-sectional approach involving 492 adolescents aged 12-21 years who had experienced victimization of relational aggression in the last three months. Analysis of moderators and mediators was used to test the hypothesis. The result shows that self-compassion does not act as a moderator and mediator. At the same time, self-criticism also does not act as a moderator but can mediate the relationship between relational aggression victimization and depression. It indicates that adolescents who get relational aggression from their friends tend to blame themselves excessively, which triggers feelings of depression. This finding indicates that adolescents tend to blame themselves after being victims of relational aggression, which eventually causes depression. Surprisingly, adolescents in Indonesia do not use self-compassion as a strategy in dealing with relational aggression by friends.